2010
DOI: 10.1186/1471-2474-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Computer work and musculoskeletal disorders of the neck and upper extremity: A systematic review

Abstract: BackgroundThis review examines the evidence for an association between computer work and neck and upper extremity disorders (except carpal tunnel syndrome).MethodsA systematic critical review of studies of computer work and musculoskeletal disorders verified by a physical examination was performed.ResultsA total of 22 studies (26 articles) fulfilled the inclusion criteria. Results show limited evidence for a causal relationship between computer work per se, computer mouse and keyboard time related to a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
155
4
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(188 citation statements)
references
References 84 publications
(215 reference statements)
10
155
4
12
Order By: Relevance
“…Furthermore, it can be questioned whether selfreported symptoms and symptoms assessed by physical examination are conceptually equal. Self-reported symptoms may, for instance, also be affected by exposure to physical or psychosocial factors at work or at home and physical examination, although protocoled, may not be that objective and may be considered a mixture of objective and subjective observations (Waersted et al 2010). This may result in misclassification for both the self-reported symptoms and the symptoms assessed by physical examination, but in different and non-systematic directions.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it can be questioned whether selfreported symptoms and symptoms assessed by physical examination are conceptually equal. Self-reported symptoms may, for instance, also be affected by exposure to physical or psychosocial factors at work or at home and physical examination, although protocoled, may not be that objective and may be considered a mixture of objective and subjective observations (Waersted et al 2010). This may result in misclassification for both the self-reported symptoms and the symptoms assessed by physical examination, but in different and non-systematic directions.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskmentioning
confidence: 99%
“…Salerno et al (2000) even stated that self-administered measures of upper extremity conditions, such as questionnaires, might be more reliable than physical examination in a population of active workers because results of the physical examination seem to depend on the job content of the study population. In a systematic review of the literature concerning the possible causal relationship between computer work and musculoskeletal symptoms of the neck and upper extremity, Waersted et al (2010) state that finding limited evidence may be partly caused by the selection of only studies with some sort of physical examination performed by a physician, physiotherapist or another trained health professional. They observed that the examination protocols and the resulting diagnoses differed substantially between the included studies.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper quadrant musculoskeletal symptoms in the working population who use visual display units (VDU) are increasing and may be as high as 74 cases per 100 persons (Lindegard et al 2012). Recommendations are usually supported by anecdotal evidence (Brewer et al 2006, Westgaard, Winkel 1997, Waersted, Hanvold & Veiersted 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Queixas musculoesqueléticas em pescoço e membros superiores são comuns entre os trabalhadores usuários de computador (WAERSTED et al, 2010). A prevalência de sintomas musculoesqueléticos em membro superior, coluna cervical e lombar entre trabalhadores usuários As CANS (Complaints of arms, neck and shoulders) podem ser definidas como queixas musculoesqueléticas nas regiões dos membros superiores, complexo do ombro e cervical não atribuídas a trauma agudo ou a desordens sistêmicas (HUISSTEDE et al, 2007).…”
Section: Queixas Musculoesqueléticas E Trabalhadores Usuários De Compunclassified